Operating budget planning for improved performance report national university of Colombia (2014)
Programming and planning is an important element in any public or private organization for appropriate administrative development, for that reason in this paper we will focus on the importance of scheduling and budget planning in a public entity. As a field of research development at the National University of Colombia in the hierarchy of the National Level was taken, because at this level you can see the execution of the operating costs which consist of personnel costs, overheads and transfers currents this in order to show that the authors involved in the construction of this program do not use existing tools for proper programming, so you want to show that if done in a conscious way , critical and realistic efficiency participating offices improve their response times and the result is optimal.